千金葦莖湯의 인체 폐암세포 증식억제에 관한 연구 - 박봉규(Bong Kyu Park); 박동일(Dong Il Park) (동의생리병리학회지, 2004)
To investigate the anti-cancer effects of aqueous extract of Cheonkumwikyung-tang (CKWKT) on the growth of human lung carcinoma cell line A549, we performed various biochemical experiments such as the effects of CKWKT on the cell proliferation and viability, the morphological changes, the effects on expression of apoptosis and cell growth-regulatory gene products. Results obtained are as follow; CKWKT treatment declined the cell viability and proliferation of A549 cells in a concentration-dependent manner. The anti-proliferative effect by CKWKT treatment in A549 cells was associated with morphological changes such as membrane shrinking and cell rounding up. CKWKT treatment induced apoptotic cell death of A549 cells in a concentration-dependent manner, which was associated with inhibition and/or degradation of apoptotic target proteins such poly(ADP-ribose) polymerase, β-catenin and phospholipase C-γ1. Western blot analysis revealed that the levels cyclin-dependent kinase inhibitor p21 expression were induced by CKWKT treatment in A549 cells. Taken together, these findings suggest that CKWKT-induced inhibition of human lung cancer cell proliferation is associated with the induction of apoptotic cell death via regulation of several major growth regulatory gene products and CKWKT may have therapeutic potential in human lung cancer. KCI Citation Count: 0